2022
DOI: 10.1371/journal.pone.0272499
|View full text |Cite
|
Sign up to set email alerts
|

MiR-31 improves spinal cord injury in mice by promoting the migration of bone marrow mesenchymal stem cells

Abstract: Background Stem cell transplantation therapy is a potential approach for the repair of spinal cord injuries and other neurodegenerative diseases, but its effectiveness is hampered by the low rate of targeted migration of cells to the area of injury. The aim of this study was to investigate the effects of miR-31 on the migration of bone marrow mesenchymal stem cells (BMSCs) and the regulation of MMP-2 and CXCR4 expression in vitro and in vivo. Methods eGFP-expressing BMSCs were isolated and cultured for subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The results of our study showed a significant improvement in the M&N group on day 1 after combined stem cell transplantation, as reflected in video and the score of stepping. This finding is surprising at first sight but is in part consistent with previous study that reported a rapid response to treatment [ 31 , 52 ]. We speculate that this may be related to the synergistic effect of NSC and MSC, and their interaction in vivo may have contributed to the rapid physiological response and functional recovery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our study showed a significant improvement in the M&N group on day 1 after combined stem cell transplantation, as reflected in video and the score of stepping. This finding is surprising at first sight but is in part consistent with previous study that reported a rapid response to treatment [ 31 , 52 ]. We speculate that this may be related to the synergistic effect of NSC and MSC, and their interaction in vivo may have contributed to the rapid physiological response and functional recovery.…”
Section: Discussionsupporting
confidence: 90%
“…Eighty-four nude mice were randomly divided into cell-free (PBS) and cell groups (hMSCs + hiPSC-NSC) (42 mice in each group), which are referred to as the Con and M&N group, respectively. Immediately after the SCI, 1 μl of PBS was injected into the injured spinal cord (1 mm rostral to the lesion epiCenter) [ 31 ] of 42 mice using a glass pipette at a rate of 0.5 μl/minute with a 10μl Hamilton syringe and a stereotaxic microinjector (RWD, Shenzhen, China). Using the same method, 42 mice were injected with 1 × 10 5 cells/μl (0.5 × 10 5 hMSCs and 0.5 × 10 5 iPSC-derived NSCs) in M&N group.…”
Section: Methodsmentioning
confidence: 99%
“…Other potential treatment strategies using implanted MSCs include promoting neural differentiation (EGF, Shh and miR-124) [ 159 , 176 , 247 , 248 ]; enhancing proliferation (bFGF, PTEN, IGF-1, and Nice4, Fig. 6 ) [ 203 , [249] , [250] , [251] ]; increasing migration ability (ChABC, Snail, miR-31 and SDF-1α) [ 250 , [252] , [253] , [254] ]; inhibiting apoptosis (GIT1 and miR-21) [ 255 , 256 ]; reducing antioxidative stress (miR-200a) [ 256 ]; proangiogensis (miR-17-5p) [ 257 ]; and neurotrophic effect (CNTF, BDNF, miR-146a-5p and miR-383) [ [258] , [259] , [260] , [261] , [262] ]. The details of these transgenic MSCs for SCI treatment are summarized in Table 2 .…”
Section: Gene Transfer Into Mscs For Neurological Disease Treatmentmentioning
confidence: 99%
“…[ 183 ] While viral‐based vector systems have been the preferred method of delivery (e.g., lentiviral [ 201 ] ), the likelihood of triggering innate microglia‐mediated immune response as well as other risks [ 202 ] has seen the progressive increase in nonviral transfection methods as an attractive alternative. [ 203 ] Several studies have reported nanoparticle‐mediated transfection of different stem cell‐modifying cargoes including siRNA, [ 204 ] miRNA, [ 205 ] and mRNA [ 206 ] typically delivered to mesenchymal (MSC) [ 196,207 ] and NSC [172a,208] prior to implantation. Several studies have demonstrated good nanoparticle‐mediated transfection efficiency into stem cells [163b,204a,206,209] .…”
Section: Nonviral Nanoparticle Delivery Of Transgenes To Different Ty...mentioning
confidence: 99%
“…[163b,204a,206,209] Genes have been delivered that help increase cell survival under hypoxic conditions, for example, through delivery of fibroblast growth factor-2 [210] or heme oxygenase-1, [211] while others direct tissue homing through delivery of inflammation-associated adhesion ligands (e.g., PSGL-1 [212] ). Other approaches include enhancing cell migration to the injured cord through delivery of miR-31 [205] and directing the differentiation of NSCs to neurons through the delivery of siRNA targeting of transcription factors, e.g., Sox9, [204] or RE-1 silencing transcription factor REST. [213] A second, less explored in vivo approach is to enhance the regenerative potential of cord resident NSCs arising from the ependymal layers surrounding the central canal.…”
Section: Therapeutic Gene Delivery To Stem Cellsmentioning
confidence: 99%